Serials Use in a College of Agriculture Education Library - Adzobu, Joseph; Opare, Juliana A. (Ghana Library Journal, 2008)
The sweep method was used to examine serials use at the Library of College of Agriculture Education, University of Education, Winneba. This involved counting in-house use by library staff during reshelving of used serials left on study tables. Data obtained mimicked Trueswell’s 80/20 rule; most of the use scores were attributable to only about 23% of serial titles studied. Serial titles available covered eight subject disciplines. Fourteen high-use serial titles out of 62 were noted; six of these were under Agriculture, the main subject of study at the College. No high-use serial title existed in the primary sciences: Mathematics, ChemistlY, Physics and Biology. High-use scores were also noted among serial titles no longer received at the Library. The second semester of the academic calendar had higher use scores than the first semester and the long vacation period had the highest monthly use scores. Factors such as the subject disciplines of titles and activities of final year students influenced use levels of ceased serial titles and the periods of high use respectively. Re-subscription of high-use titles no longer received. collection of new serial titles for the primary sciences and use of eresources through CARLIGH (if print serials could not be procured) were recommended. Also recommended was a continued monitoring of serials use at the library so as to have a high-use serials stock.